PEMETAAN KARAKTERISTIK FISIKA TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA PAK BULU KABUPATEN MEMPAWAH - Fadhly, Zafhaizar; Junaidi, Junaidi; Hazriani, Rini (Agros Journal of Agriculture Science, 2024)
This research aims to map and provide information related to the characteristics of soil physical properties on rice fields, secondary forests, and oil palm plantations in Pak Bulu Village, Mempawah Regency with a total area of 99.87ha. This research uses the geographic random system method by categorizing soil physical properties in each land unit using the ArcGIS application. The implementation of this activity was carried out by taking soil samples as many as 11 sample points on 6 land units and then analyzed in the laboratory. Stages in the research are data processing, map making and presentation of results. The results showed different characteristics in each land use, which in paddy fields have loamy soil texture, clayey loam to silty loam, low bulk density, high field capacity moisture content, porous soil total porosity and moderate to rather slow permeability. Secondary forest land use has a loamy to sandy loam soil texture, medium bulk density, medium field capacity moisture content, good to poor total soil porosity, moderately slow to fast soil permeability, and oil palm plantation land use has a sandy loam soil texture, medium to high bulk density, moderate field capacity moisture content, poor total soil porosity, and moderately slow soil permeability.